Molecular analysis of an increase in trimethoprim/sulfamethoxazole-resistant MRSA reveals multiple introductions into a tertiary care hospital, Germany 2012-19 - Nurjadi, Dennis; Klein, Sabrina; Hannesen, Julius; Heeg, Klaus; Boutin, Sébastien; Zanger, Philipp (The journal of antimicrobial chemotherapy, 2022)
Increasing spread of resistance could jeopardize the use of antifolates against MRSA infections.We compared the prevalence of phenotypic trimethoprim/sulfamethoxazole resistance in 20534 clinical Staphylococcus aureus isolates (19096 MSSA and 1438 MRSA) of non-redundant patients at Heidelberg University Hospital over 8 years and performed WGS on trimethoprim/sulfamethoxazole-resistant MRSA.From 2012 to 2019, trimethoprim/sulfamethoxazole resistance in MSSA (674/19096; 3.5%) ranged between 1.5% and 7.2% and in MRSA (135/1438; 9.4%) between 0.5% and 20.2%, reaching a peak in 2016 and 2018, respectively (Ptrend<0.001). Trimethoprim/sulfamethoxazole resistance was more likely in outpatients than inpatients (P=0.005), younger patients (P<0.001), skin and soft tissue infections (SSTIs) (MRSA only, P=0.05), submissions from pulmonology (MRSA only, P=0.001), the upper respiratory tract (MSSA only, P<0.001) and general surgery (MSSA only, P=0.001). WGS of 76 trimethoprim/sulfamethoxazole-resistant MRSA revealed that 59% belonged to major pandemic CA-MRSA clones (ST22, ST8, ST398, ST772, ST30), 47% harboured Panton-Valentine leucocidin (PVL), 97% SCCmec IV/V, 71% dfrG and 28% dfrA. SNP-based phylogeny of trimethoprim/sulfamethoxazole-resistant MRSA core genomes favoured independent introduction over clonal expansion as the source, most prominently of dfrA+ trimethoprim/sulfamethoxazole-resistant ST22 MRSA from the Gaza Strip.The presented results support that trimethoprim/sulfamethoxazole-resistant S. aureus, formerly associated with SSTI from outpatients and S. aureus in the (sub)tropics, is on the rise in the temperate zone, potentially due to migration. Closer monitoring of trimethoprim/sulfamethoxazole resistance in S. aureus is recommended to safeguard the effectiveness of antifolate compounds.